Human activities accelerated the degradation of saline seepweed red beaches by amplifying top‐down and bottom‐up forces. Issue 7 (23rd July 2018) - Lu, Weizhi; Xiao, Jingfeng; Lei, Wei; Du, Jinqiu; Li, Zhengjie; Cong, Pifu; Hou, Wenhao; Zhang, Jialin; Chen, Luzhen; Zhang, Yihui; Liao, Guoxiang
Abstract: Salt marshes dominated by saline seepweed ( Suaeda heteroptera ) provide important ecosystem services such as sequestering carbon (blue carbon), maintaining healthy fisheries, and protecting shorelines. These salt marshes also constitute stunning red beach landscapes, and the resulting tourism significantly contributes to the local economy. However, land use change and degradation have led to a substantial loss of the red beach area. It remains unclear how human activities influence the top‐down and bottom‐up forces that regulate the distribution and succession of these salt marshes and lead to the degradation of the red beaches. We examined how bottom‐up forces influenced the germination, emergence, and colonization of saline seepweed with field measurements and a laboratory experiment. We also examined whether top‐down forces affected the red beach distribution by conducting a field survey for crab burrows and density, laboratory feeding trials, and waterbird investigations. The higher sediment accretion rate induced by human activities limited the establishment of new red beaches. The construction of tourism facilities and the frequent presence of tourists reduced the density of waterbirds, which in turn increased the density of crabs, intensifying the top‐down forces such as predators and herbivores that drive the degradation of the coastal red beaches. Our results show that sediment accretion and plant–herbivory changes induced by human activities were likely the two primary ecological processes leading to the degradation of the red beaches. Human activities significantly shaped the abundance and distribution of the red beaches by altering both top‐down and bottom‐up ecological processes. Our findings can help us better understand the dynamics of salt marshes and have implications for the management and restoration of coastal wetlands.